2018
DOI: 10.1002/bdr2.1188
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc levels in Ecuadorian mothers of infants with nonsyndromic cleft lip with or without cleft palate: A case series

Abstract: Background: Previous studies have reported an association between maternal zinc deficiency and increased risk of nonsyndromic cleft lip with or without cleft palate (NSCL/P) in offspring. A high prevalence of zinc deficiency and a high prevalence of NSCL/P have been reported in Ecuador. We postulated that mothers of infants with NSCL/P may have lower serum zinc levels than women from the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Copper injection and low zinc diet during pregnancy were also linked to orofacial clefts [48][49][50]. The case-series results published in 2018 supported previous results, that low plasma zinc levels of healthy mothers were associated with nonsyndromic cleft lip/palate among their babies [51]. More recently, a case-control study confirmed that exposure to a high level of zinc during pregnancy was associated with reduced risk of cleft lip and/or palate [52].…”
Section: Role Of Zinc Deficiency In Cleft Lip Cleft Palate and Salivmentioning
confidence: 53%
“…Copper injection and low zinc diet during pregnancy were also linked to orofacial clefts [48][49][50]. The case-series results published in 2018 supported previous results, that low plasma zinc levels of healthy mothers were associated with nonsyndromic cleft lip/palate among their babies [51]. More recently, a case-control study confirmed that exposure to a high level of zinc during pregnancy was associated with reduced risk of cleft lip and/or palate [52].…”
Section: Role Of Zinc Deficiency In Cleft Lip Cleft Palate and Salivmentioning
confidence: 53%
“…It is important to mention that in a previous report following the same methodology, we evaluated PZn levels in a cohort of 35 women who had a child between 1 and 12-months-old with an oral malformation, reporting a prevalence of ZD of 31.4; these results were probably due to the use of formula to feed the children because the oral malformation causes breastfeeding difficulties [ 20 ]. Lactation is a risk factor for zinc deficiency and the recommended dietary allowance is higher among pregnant and lactating women than in non-pregnant non-lactating women [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we excluded pregnant women, non-fasting women, women with any disability that interferes with sample collection, and women who consumed alcohol or performed extreme exercise the night before sampling, factors that were contemplated by ENSANUT-ECU. We followed these guidelines following the methodology of a previous report of our research group [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations